Business in the U.S. Democracy - Solymossy, Emeric (Review of European and Comparative Law, 2020)
This paper discusses a model of business in a “democracy” by identifying the three underlying concepts; the individual, the collective (society), and the government (system and mechanics). Furthermore, each of these elements is also a multi-factor construct. The foundations and development of the United States is discussed. The exploration, discovery and development of any new country require risk taking and innovative behavior, which was instrumental in the creation of heroes and myths, which shaped much of the culture. From this background, some of the principle characteristics of the entrepreneur are explored and correlated to some generally accepted measures of national culture. The concepts are developed; their inter-relationships and the resulting dynamics are presented. The foundation(s) and uniqueness of the U.S. form of democracy is explored as a government typology. Data is presented exhibiting the variability of business confidence, and a conclusion is reached that the attitudes and policies of the government have a greater impact on business formation and success than the form of government.